Dissecting the genome-wide genetic variants of milling and appearance quality traits in rice - Misra, Gopal; Anacleto, Roslen; Badoni, Saurabh; Butardo, Vito; Molina, Lilia; Graner, Andreas; Demont, Matty; Morell, Matthew K.; Sreenivasulu, Nese (Oxford University Press, 2019)
Genetic regions in the rice genome are identified that affect the proportion of grains that remain intact after milling (the head rice yield) and the degree of chalkiness in the grain.